Geological materials testing and uncertainty calculations: a simple GUM-based algorithm - Xirouchakis, D.; Bouzinos, A. (Bulletin of the Geological Society of Greece, 2013)
We have applied a simple GUM-based procedure to estimate the uncertainties of physical and mechanical properties in geological materials. First, we define the quantity to measure and decide whether we want to work with units or relative quantities. Subsequently, we calculate the repeatability standard deviation (sr) and the standard uncertainty. If we have proficiency test data or use certified reference materials, we use them to estimate the laboratory bias, the reproducibility standard deviation (sR) and the reproducibility standard uncertainty. We also make sure that we know or have estimated the standard uncertainty of the instruments that we use in the measurements. The latter is typically taken from the instrument calibration or precision statement. We estimate the standard uncertainty of the reference materials and the standard uncertainty of the laboratory bias. The final two steps include the calculation of (1) the laboratory standard uncertainty uncorrected for bias and corrected for bias, and (2) the laboratory expanded uncertainty at the 95% confidence limit.